EXPERIMENTAL DETERMINATION OF CADMIUM UPTAKE IN SHELLS OF THE PLANKTONIC FORAMINIFERA ORBULINA UNIVERSA AND GLOBIGERINA BULLOIDES: IMPLICATIONS FOR SURFACE WATER PALEORECONSTRUCTIONS - Mashiotta T.A.; Lea D.W.; Spero H.J. (My University, 1997)
Laboratory culturing is a direct means of determining Cd uptake in shells of planktonic foraminifera. We employed a new stable isotope technique using both 110Cd and 111Cd to assess uptake in the symbiont bearing species, Orbulina universa, and the nonsymbiont bearing species, Globigerina bulloides. In certain experiments with G. bulloides the three endmember isotope dilution method was combined with a recently described 48Ca labeling technique.Shells of Orbulina universa cultured under a 12 h high light:12 h dark cycle are found to incorporate very little Cd. Foraminifera can be induced to take up slightly more Cd by growth under 24 h darkness or under a 12 h high light:12 h dark cycle with exposure to the photosynthesis inhibitor, DCMU. These results demonstrate that O. universa under-represents the Cd concentration of seawater in which the shell is precipitated. Additionally, the results suggest a previously unknown influence of symbiotic dinoflagellates on foraminiferal shell chemistry. There are two different mechanisms by which symbionts might play a role in influencing Cd uptake in O. universa: (1) algal sequestration and removal of Cd from the foraminiferal calcification microenvironment or (2) photosynthetic enhancement of calcification rate, leading to Cd exclusion. If these results apply generally to bioactive trace metal uptake by dinoflagellate-bearing planktonic foraminifera, they suggest that shells of species such as O. universa only record qualitative changes in surface water metal concentrations. The response for Cd uptake in nonsymbiont bearing G. bulloides (cultured under a 12 h high light:12 h dark cycle) appears linear within and slightly above the range of Cd concentrations found in the modern ocean, with an effective partition coefficient equal to 1.9 +/- 0.2 (95% C.I.). The Cd partition coefficient determined for G. bulloides falls within the range of DCd previously found for fossil benthic foraminifera but is twenty times higher than that for O. universa (DCd = 0.095 +/- 0.021 (95% C.I.)) grown under identical culture conditions. Because G. bulloides appears to reliably record seawater Cd concentrations, it should be suitable for accurate paleoreconstructions of surface water Cd and PO3-4 concentrations.